PAK6 Phosphorylates 14-3-3γ to Regulate Steady State Phosphorylation of LRRK2 - Civiero, Laura; Cogo, Susanna; Kiekens, Anneleen; Morganti, Claudia; Tessari, Isabella; Lobbestael, Evy; Baekelandt, Veerle; Taymans, Jean-Marc; Chartier-Harlin, Marie-Christine; Franchin, Cinzia; Arrigoni, Giorgio; Lewis, Patrick A.; et al. (Frontiers in Molecular Neuroscience, 2017)
Mutations in Leucine-rich repeat kinase 2 (LRRK2) are associated with Parkinson’s disease (PD) and, as such, LRRK2 is considered a promising therapeutic target for age-related neurodegeneration. Although the cellular functions of LRRK2 in health and disease are incompletely understood, robust evidence indicates that PD-associated mutations alter LRRK2 kinase and GTPase activities with consequent deregulation of the downstream signaling pathways. We have previously demonstrated that one LRRK2 binding partner is P21 (RAC1) Activated Kinase 6 (PAK6). Here, we interrogate the PAK6 interactome and find that PAK6 binds a subset of 14-3-3 proteins in a kinase dependent manner. Furthermore, PAK6 efficiently phosphorylates 14-3-3γ at Ser59 and this phosphorylation serves as a switch to dissociate the chaperone from client proteins including LRRK2, a well-established 14-3-3 binding partner. We found that 14-3-3γ phosphorylated by PAK6 is no longer competent to bind LRRK2 at phospho-Ser935, causing LRRK2 dephosphorylation. To address whether these interactions are relevant in a neuronal context, we demonstrate that a constitutively active form of PAK6 rescues the G2019S LRRK2-associated neurite shortening through phosphorylation of 14-3-3γ. Our results identify PAK6 as the kinase for 14-3-3γ and reveal a novel regulatory mechanism of 14-3-3γ/LRRK2 complex in the brain.